Molecular Dynamics Simulation of the Thermosensitive Gelation Mechanism of Phosphorylcholine Groups-Conjugated Methylcellulose Hydrogel - Hongyu Mei; Yaqing Huang; Juzhen Yi; Wencheng Chen; Peng Guan; Shanyue Guan; Xiaohong Chen; Wei Li; Liqun Yang (Gels)
The intelligently thermosensitive 2-methacryloyloxyethyl phosphorylcholine (MPC) groups-conjugated methylcellulose (MC) hydrogel, abbreviated as MPC-g-MC, exhibits good potential for prevention of postoperative adhesions. However, its thermosensitive gelation mechanism and why the MPC-g-MC hydrogel shows a lower gelation temperature than that of MC hydrogel are still unclear. Molecular dynamics (MD) simulation was thus used to investigate these mechanisms in this work. After a fully atomistic MPC-g-MC molecular model was constructed, MD simulations during the thermal simulation process and at constant temperatures were performed using GROMACS 2022.3 software. The results indicated that the hydrophobic interactions between the MPC-g-MC molecular chains increased, the interactions between the MPC-g-MC molecular chains and H2O molecules decreased with the rise in temperature, and the hydrogen bonding structures were changed during the thermal simulation process. As a result, the MPC-g-MC molecular chains began to aggregate at about 33 °C (close to the gelation temperature of 33 °C determined by the rheological measurement), bringing about the formation of the MPC-g-MC hydrogel in the macroscopic state. The mechanism of MPC-g-MC hydrogel formation showed that its lower gelation temperature than that of the MC hydrogel is attributed to the increase in the interactions (including hydrophobic interactions, hydrogen bonding interactions, Van der Waals and Coulomb forces) induced by the side MPC groups of MPC-g-MC molecules. The thermosensitive gelation mechanism revealed in this study provides an important reference for the development of novel thermosensitive MC-derived hydrogels with gelation temperatures close to human body temperature.